Communication Patterns of Parents with Migrating Students - Zein, Aina Safitri (Psikologiya Journal, 2024)
Being a student often requires individuals to face situations where they have to be away from their parents, known as migration. Due to the distance created by migration, students who migrate face limitations in terms of communication. Communication is a crucial aspect of human life, especially between parents and children. In this study, researchers aim to gather information on the communication patterns of parents with migrating students. Additionally, the study aims to understand how students maintain their communication relationships with their parents despite the distance. The study includes 50 participants who meet the criteria of being active students. Data was collected through open-ended questionnaires and analyzed thematically. The results indicate a significant positive relationship between migrating students and negative feelings, while non-migrating students experience positive feelings. The communication patterns of migrating students with their parents can be observed through the intensity of communication. Students who communicate more frequently feel less lonely, become independent individuals, and gain new experiences. On the other hand, students who communicate less often with their parents tend to feel lonely.